A JOURNEY IN WRITING FOR SCHOLARLY PUBLICATIONS - Tee, E.R. (Malaysian Journal of Library and Information Science, 1999)
Writing for scholarly publications is usually difficult for the first time. A thorough understanding and mastering of the subject matter, a good command of the language, and adept in following the style of the publication are important. Proper guidance and structured training can help in setting a course to successful writing. The publication achievements of a postgraduate student in a three-year duration since attending a technical writing workshop are analysed. This paper presents a brief analysis of the publications and suggests some ideas for achievements.